This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: 10 ( y ) as the value of the exponent when y is expressed in base 10 . Such interpretation gives that 10 log 10 ( x ) = x, and log 10 (10 x ) = x. In addition, with the laws of exponents, we see that log 10 ( xy ) = exponent when xy is written in base 10 = sum of exponents when x and y are written in base 10 = log 10 ( x ) + log 10 ( y ) . Similarly, we have log 10 ( x/y ) = log 10 ( x ) − log 10 ( y ) , and log 10 ( x r ) = r log 10 ( x ) . Therefore, log 10 ( x + y ) n = log 10 ( x ) + log 10 ( y ) , and log 10 ( x − y ) n = log 10 ( x ) − log 10 ( y ) . The above discussion also applies to other bases such as 2, e. I give below a diagram of the graphs of y = exp( x ) and its inverse y = ln( x ). y x 4 4 2 2-2-4-2-4 y = exp(x) y = ln(x) y=x...
View Full Document